The Effect Of Transformational Leadership On Turnover Intention: The Mediating Role Of Work Stress And Organizational Commitment In The Retail Industry - Sofia Apriliani Penu Sukalumba; Abdul Haeba Ramli (Jurnal Ilmiah Manajemen Kesatuan, 2025)
This study aims to analyze the influence of transformational leadership on turnover intention, considering the mediating roles of work stress and organizational commitment among retail industry employees. The research employed a quantitative approach using Partial Least Squares-Structural Equation Modeling (PLS-SEM), involving 155 respondents working at PT Duta Intiguna Yasa (Mr.DIY) in East Jakarta, Bogor, and Depok. The results indicate that transformational leadership does not have a direct effect on turnover intention, but it does exert an indirect influence through two pathways: the reduction of work stress and the enhancement of organizational commitment. Organizational commitment emerged as a stronger mediator in reducing turnover intention, while work stress also played a significant yet weaker mediating role. Meanwhile, the indirect effect of work stress on turnover intention through organizational commitment, as well as the combined dual mediation pathway, was not statistically significant. These findings underscore the importance of developing transformational leadership to foster employee loyalty. Practical implications include leadership training, effective stress management strategies, and efforts to strengthen organizational commitment in order to improve employee retention in the retail sector.   Keywords: Transformational Leadership, Turnover Intention, Work Stress, Organizational Commitment, Retail Industry